Representative elementary volume (REV) of cementitious materials from three-dimensional pore structure analysis. (December 2017) - Yio, M.H.N.; Wong, H.S.; Buenfeld, N.R.
Abstract: The representative elementary volume (REV) is a fundamental property of a material, but no direct measurements exist for cementitious materials. In this paper, the REV of cement pastes with supplementary cementitious materials (GGBS, PFA, SF) was determined by analysing the three-dimensional pore structure (> 0.2 μm) using laser scanning confocal microscopy (LSCM). The effect of axial distortion inherent to LSCM on 3D pore structure was also investigated. A range of 3D pore parameters was measured using skeletonisation, maximal ball and random walker algorithms. Results show that axial distortion has insignificant effects on most parameters except Euler connectivity, average pore and throat volumes and directional diffusion tortuosities. Most pore parameters become independent of sampling volume at ≈ 60 3 μm 3 except diffusion tortuosities and formation factor. The REV for porosity calculated based on a statistical approach at eight realisations and 5% relative error was found to be ≈ 100 3 μm 3 .